Hydrogel-Based Nanocomposites and Mesenchymal Stem Cells: A Promising Synergistic Strategy for Neurodegenerative Disorders Therapy - Diego Albani; Antonio Gloria; Carmen Giordano; Serena Rodilossi; Teresa Russo; Ugo D’Amora; Marta Tunesi; Alberto Cigada; Luigi Ambrosio; Gianluigi Forloni (The Scientific World Journal)
Hydrogel-based materials are widely employed in the biomedical field. With regard to central nervous system (CNS) neurodegenerative disorders, the design of injectable nanocomposite hydrogels for in situ drug or cell release represents an interesting and minimally invasive solution that might play a key role in the development of successful treatments. In particular, biocompatible and biodegradable hydrogels can be designed as specific injectable tools and loaded with nanoparticles (NPs), to improve and to tailor their viscoelastic properties upon injection and release profile. An intriguing application is hydrogel loading with mesenchymal stem cells (MSCs) that are a very promising therapeutic tool for neurodegenerative or traumatic disorders of the CNS. This multidisciplinary review will focus on the basic concepts to design acellular and cell-loaded materials with specific and tunable rheological and functional properties. The use of hydrogel-based nanocomposites and mesenchymal stem cells as a synergistic strategy for nervous tissue applications will be then discussed.